Hubungan Dukungan Orang Tua dengan Kesiapan Anak Remaja Putri Menghadapi Menarche di SD Negeri Dukuh 01 Mojolaban Sukoharjo - Gus Prasetyo, Mukhlis, Winarsih Nur A, S.Kep.Ns.,ETN,M.Kep, Endang Zulaicha S.,S.Kp.,M.Kep (2016)
Menstruation which first called the menarche and average occurs at age 12-16 years. Teenagers who are lack support from parents which is support information, an emotional, appreciation, and instrumental regarding menstruation, is a very bad experience. The conditions indicates that many teenagers who have less preparedness in facing menarche. The preparation is necessary, because the feelings of anxiety and fear it would appear when a lack of understanding about the teenagers menarche. For that reason, teenagers need to be prepared to face the arrival of menarche. The purpose of research was to determine the relationship between support parents with teenagers preparedness face menarche in female student Public Elementary School 01 of dukuh hamlet Mojolaban Subdistrict Sukoharjo District. Type of research used in this research quantitative by using the correlation method with cross sectional approach. The population in this research is all of female students grade IV, V, and VI which not having yet menstrual cycles many as 38 of female students. The sample used in this research total sampling many as 38 of female students. The instrument used a questionnaire. Data analysis used Spearman Rank Test (Rho) with the result shows p value = 0,001 that Ho is rejected (p <0.05), it shows there areis a correlation between support parents with teenagers preparedness in face menarche in Public Elementary School 01 of dukuh hamlet Mojolaban Subdistrict Sukoharjo District. Advice for further research are expected to undertake further research into the sub-variables of the support of parents which includes information support, an emotional, appreciation, and the instrumental should be in detail, in order to determine sub-variable support are most influence on teenagers preparedness in face menarche.